PERANCANGAN BUKU DOA UNTUK ANAK-ANAK - Almaratul Muntaz; Yayan Hariansyah; Aryanto Aryanto (Besaung : Jurnal Seni Desain dan Budaya, 2016)
Children are a new generation successor to the ideals of family, religion, race and country. Kids are human resources. Instill good morals to children is essential for the creation of the next generation a good one way to get the kids to pray to the creator God subhanahuwata'ala, as the prayer itself is God's command. For those reasons, the prayer book is designed for children as a medium of learning about prayer, knowledge of Islam, stories and games, so that children can learn to pray with fun.